Hit Identification and Functional Validation of Novel Dual Inhibitors of HDAC8 and Tubulin Identified by Combining Docking and Molecular Dynamics Simulations - Antonio Curcio; Roberta Rocca; Federica Chiera; Maria Eugenia Gallo Cantafio; Ilenia Valentino; Ludovica Ganino; Pierpaolo Murfone; Angela De Simone; Giulia Di Napoli; Stefano Alcaro; Nicola Amodio; Anna Artese (MDPI AG, 2024)
Chromatin organization, which is under the control of histone deacetylases (HDACs), is frequently deregulated in cancer cells. Amongst HDACs, HDAC8 plays an oncogenic role in different neoplasias by acting on both histone and non-histone substrates. Promising anti-cancer strategies have exploited dual-targeting drugs that inhibit both HDAC8 and tubulin. These drugs have shown the potential to enhance the outcome of anti-cancer treatments by simultaneously targeting multiple pathways critical to disease onset and progression. In this study, a structure-based virtual screening (SBVS) of 96403 natural compounds was performed towards the four Class I HDAC isoforms and tubulin. Using molecular docking and molecular dynamics simulations (MDs), we identified two molecules that could selectively interact with HDAC8 and tubulin. CNP0112925 (arundinin), bearing a polyphenolic structure, was confirmed to inhibit HDAC8 activity and tubulin organization, affecting breast cancer cell viability and triggering mitochondrial superoxide production and apoptosis.